Idioma inglés y su relación con el desempeño profesional de los docentes del CENID-UTB período académico 2022 - Sisa Llumitaxi, Estalin Yoel (2022)
The present case study focused on the English language and its relationship with the job performance of the teachers of the Language Center of the Technical University of Babahoyo, academic period 2022, starting from the current perspective, this language is considered as the universal language. That leads the great educational, commercial, social, labor scenarios, among others; that generate millionaire income in the world. The inefficient application of methodological strategies for the teaching of English by CENID educators limits student learning and decreases the job performance of teachers. The poor use of technology in the work activities of the teacher and the poor relationship between co-workers of this academic unit, maintain a current problem in this unit and as a solution measure, the training of teachers in methodology issues for the teaching of English, the use of technological tools and human relations to boost the work environment and improve the quality of service offered by educators.